The life of Alexander the Great - Saunders, Nicholas J. (Columbus, OH : School Specialty Pub., 2006)
Presents a graphic novel of the life and military conquests of Alexander the Great who became king of Macedonia after the assassination of his father, Philip II in 336 B.C.
Includes index.
5.0
3-6
Keywords: Alexander, -- the Great, -- 356-323 B.C. -- Comic books, strips, etc. -- Juvenile literature; Greece -- History -- Macedonian Expansion, 359-323 B.C. -- Comic books, strips, etc. -- Juvenile literature; Generals -- Greece -- Biography -- Comic books, strips, etc. -- Juvenile literature; Greece -- Kings and rulers -- Biography -- Comic books, strips, etc. -- Juvenile literature; Alexander, -- the Great, -- 356-323 B.C. -- Cartoons and comics; Greece -- History -- Macedonian Expansion, 359-323 B.C. -- Cartoons and comics; Generals -- Cartoons and comics; Kings, queens, rulers, etc. -- Cartoons and comics; Cartoons and comics; Alexander, -- the Great, -- 356-323 B.C. -- Comic books, strips, etc; Greece -- History -- Comic books, strips, etc; Generals -- Greece -- Biography -- Comic books, strips, etc; Kings and rulers -- Biography -- Comic books, strips, etc; Comic books, strips, etc